2003
DOI: 10.1016/s0009-2541(03)00200-6
|View full text |Cite
|
Sign up to set email alerts
|

Residence and redistribution of REE, Y, Zr, Th and U during granulite-facies metamorphism: behaviour of accessory and major phases in peraluminous granulites of central Spain

Abstract: Accessory minerals are thought to play a key role in controlling the behaviour of certain trace elements such as REE, Y, Zr, Th and U during crusta 1 melting processes under high-grade metamorphic conditions. Although this is probably the case at middle crustal levels, when a comparison is made with granulite-facies lower crustal levels, differences are seen in trace element behaviour between accessory minerals and some major phases. Such a comparison can be made in Central Spain where two granulite-facies ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 55 publications
2
41
0
1
Order By: Relevance
“…In contrast, high field-strength elements (HFSE) and rare earth elements (REE) are relatively immobile during metamorphism, and in general tend to reflect igneous processes (Middelburg et al, 1988). However, during granulite facies metamorphism, Y, Zr, Th, U and REEs may also be modified (e.g., Bea and Montero, 1999;Villaseca et al, 2003). In this study, fresh samples were mostly selected from the margins of dykes/sills, and some from the centers; one sample was from a pegmatite vein in the Longwangtang sill (sample 07DX11), and another was from a pyroxenite enclave in the same pegmatite vein in this sill (sample 07DX10) (all indicated in Table 1).…”
Section: Significance Of Whole-rock Compositionsmentioning
confidence: 99%
“…In contrast, high field-strength elements (HFSE) and rare earth elements (REE) are relatively immobile during metamorphism, and in general tend to reflect igneous processes (Middelburg et al, 1988). However, during granulite facies metamorphism, Y, Zr, Th, U and REEs may also be modified (e.g., Bea and Montero, 1999;Villaseca et al, 2003). In this study, fresh samples were mostly selected from the margins of dykes/sills, and some from the centers; one sample was from a pegmatite vein in the Longwangtang sill (sample 07DX11), and another was from a pyroxenite enclave in the same pegmatite vein in this sill (sample 07DX10) (all indicated in Table 1).…”
Section: Significance Of Whole-rock Compositionsmentioning
confidence: 99%
“…7). The high modal proportions of feldspar in SCS granulite xenoliths together with the scarcity of monazite (Villaseca et al, 2003), suggests that feldspars control virtually the entire LREE-Eu budget.…”
Section: An Intergranular Zircon Crystal Is Shown At Right (Granulitementioning
confidence: 99%
“…It has been observed that the modal amount of zircon, monazite and apatite decreases dramatically with increasing metamorphic grade (Reid, 1990;Bea and Montero, 1999) and other accessory minerals (e.g. xenotime) are completely con sumed before extreme granulite conditions are reached (Villaseca et al, 2003). Nevertheless, SCS granulite xenoliths show Zr and REE contents mostly in the range of 155 to 280 and 120 to 225 ppm, respectively, similar to peraluminous metamorphic rocks from outcropping migmatite terranes.…”
Section: Scs Residual Granulites Undepleted In Zr-reementioning
confidence: 99%
See 1 more Smart Citation
“…Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) has become one of the most useful in-situ analytical tools for geological materials over the past few years, even though it has a relatively lower sensitivity than secondary ion mass spectrometry (SIMS) because of elemental fractionations (Longerich et al, 1996;Norman et al, 1996;Chen et al, 1997;Eggins et al, 1998;Ridley, 2000;Becker and Tenzler, 2001;Villaseca et al, 2003;Zack et al, 2002;Cox and Witon, 2003;Kabashima et al, 2003;Cocherie and Robert, 2008;Frei and Gerdes, 2009). The advantages of the LA-ICP-MS technique are fast in-situ analysis, low sample consumption, and lack of polyatomic interference species (Rusoo et al, 2002;Ishida et al, 2004).…”
Section: Introductionmentioning
confidence: 99%